3d Printing with Biopolymers - Garmulewicz, A (Elsevier, 2023)
This chapter presents how 3D printing biopolymers can enable a circular economy. We focus on 3D printing as a technology for distributed production, how the use of biopolymers from second and third-generation biomass such as food waste and algae can ensure that sourcing is regenerative and non-extractive, and the need for comprehensive life-cycle assessment. The technical means by which 3D printing can be adapted to and can add functionality to biopolymers is discussed. A case study on extracting chitin-cellulose biopolymer formulations from local biomass is provided, offering a view toward regenerative production for a circular economy. The future of 3D printing biopolymers for the circular economy is discussed, with an emphasis on improving material performance and developing scalable regenerative supply chains. © 2023 Elsevier Inc. All rights reserved.